Study of activities at Jurong Port main gate (general and bulk cargo) - Koh, Joanna Siok Khim. (2011)
Singapore, being an International Maritime Centre (IMC), is renowned as a container transhipment hub. Besides containers, the general and bulk cargoes make up the other important aspect of the maritime industry. This project focuses on Jurong Port (JP). JP is Singapore’s multi-purpose port. JP has two gates: the Main Gate which specialises in general and bulk cargo and the West gate which specialises in containers. Unlike PSA whose Flow-Through Gate system is a fully automated system, JP’s Main Gate is only partially automated. This project investigates the documentation of the outbound Main Gate. Also, a study will be done on the safety and security measures undertaken by JP. A small case study is conducted on one of JP’s cement customers, Holcim. The agreement between Jurong Port and Holcim has mutually benefited both parties. Lastly, analysis of the queues, arrival rates and services times at the gate for the outbound traffic for one typical day will be done. Using the queuing method, an assumption is made that the arrivals at each lane at the outbound gate are Poisson and the service times are exponentially distributed. Lastly, conclusions will be made, followed by recommendations such as diverting traffic, introducing peak fees and installing electronic sign boards.